Denis Provencher. Queer Maghrebi French: Language, Temporalities, Transfiliations. Liverpool: Liverpool UP, 2017. - Alvaro Luna (Studies in 20th & 21st Century Literature, 2018)
Review of Denis Provencher. Queer Maghrebi French: Language, Temporalities, Transfiliations. Liverpool: Liverpool UP, 2017. 314 pp.
Keywords: Maghrebi; Queer; French; Provencher